NILAI PERUSAHAAN PADA PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) : KAJIAN SISTEMATIS - Erika Puspita Sari; Dwi Cahyono; Rendy Mirwan Aspirandi (Universitas Nusa Cendana, 2021)
The value of the company has an important role in describing the level of public trust in a company. The purpose of this literature review is to determine the factors that affect the value of BUMN companies and how to solve them. A systematic study was carried out using a Systematic Literature Review approach in journals published from 2016 to 2020 which concluded that the value of BUMN companies in Indonesia was still low in their management capabilities. The causes of the low value of BUMN companies include 1) BUMN companies that do not pay attention to the components of intellectual capital they have, 2) excessive debt 3) Weak implementation of GCG 4) the occurrence of deviations by BUMN directors and 5) exposure and other risks. The solution to overcome this problem is that state-owned companies must create a competitive advantage so that market perceptions will increase and the company can survive in a dynamic business environment. How: 1) By utilizing all potential resources, namely human capital, physical capital, and structural capital to generate added value. 2) managing as efficiently and effectively as possible in order to generate profits as expected by investors and 3) making specific GCG practice guidelines for SOEs and 4) implementing debt policies, hedging and risk management such as financial risks, market risks and business risks . That way the company is not burdened by the weakening of the rupiah exchange rate against debt risk and is able to manage foreign currency assets. Keywords: Systematic Literature Review; Value of BUMN Companies